Effect of Loading Frequency on Fatigue Behavior of Magnesium Alloy in Humid Environment - Sajuri, Zainuddin; Miyashita, Yukio; Mutoh, Yoshiharu (2006)

(untitled)
Effect of loading frequency on fatigue behavior of an extruded AZ61 magnesium alloy was investigated at 50? -80%RH environment. The frequencies applied were 1 and 10 Hz. It was found that at stresses below the fatigue limit (at 20? -55%RH), the fatigue fracture was time dependent where fatigue lives for both frequencies were almost identical. In contrast, the fatigue fracture in the region higher than the fatigue limit was dominated by the number of loading cycles. Fatigue fracture at low stress amplitudes for both frequencies were originated from the corrosion pit formed on the surface. Effect of frequency on fatigue crack growth behavior was also investigated. The results showed that in the near-threshold region, the 1 Hz frequency demonstrated higher fatigue crack growth resistance compared to the 10 Hz.